Karakteristik dan Klasifikasi Anak Berkebutuhan Khusus Secara Mental Emosional dan Akademik - Puti Artistia; Olfa Seviona Putri; Nurhaliza Nurhaliza; Opi Andriani (Dharma Acariya Nusantara: Jurnal Pendidikan, Bahasa dan Budaya, 2024)
This research aims to determine the characteristics of students with special needs, in inclusive schools.  The methods used were observation, interviews and documentation, after which the data was analyzed descriptively qualitatively. Social and communication development is the most important disorder, as in normal individuals, disorders of verbal intelligence or language and difficulties in continuously renewing behavior, desires, pleasures and habits.  Based on interview findings, observations and literature, it shows that child with special needed show characteristics in the areas of communication, social interaction, sensory abilities, playing styles, behavior and feelings.the child with special needed show characteristics in the areas of communication, social interaction, sensory abilities, play styles, behavior and emotions.